Activation of microglia and induction of pro-inflammatory cytokines in the hippocampus of type 2 diabetic rats. (September 2014) - Hwang, In Koo; Choi, Jung Hoon; Nam, Sung Min; Park, Ok Kyu; Yoo, Dae Young; Kim, Woosuk; Yi, Sun Shin; Won, Moo-Ho; Seong, Je Kyung; Yoon, Yeo Sung
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: The majority of immune cells in the brain are comprised of microglia, which undergo morphological changes when activated to remove damaged neurons and infectious agents from the brain tissue. In this study, we investigated the effects of type 2 diabetes on microglial activation and the subsequent secretion of pro-inflammatory cytokines, such as interferon-gamma (IFN-gamma) and interleukin-1beta (IL-1beta), in the hippocampus using Zucker diabetic fatty (ZDF) rats and Zucker lean control (ZLC) rats at various diabetic stages. Methods: Zucker lean control and Zucker diabetic fatty rats were sacrificed at 12 (early diabetic stage), 20, or 30 weeks of age (chronic diabetic stage), and the hippocampus was obtained via transcardiac perfusion or dissection for immunohistochemistry and western blot analysis, respectively. Results: Zucker diabetic fatty rats demonstrated significantly higher glucose levels at 12 and 30 weeks of age compared to ZLC rats. Microglia immunoreactive to ionized calcium-binding adapter molecule 1 (Iba-1) had hypertrophied cytoplasm with retracted processes at 30 weeks of age. In contrast, Iba-1-immunoreactive microglia displayed similar morphology in ZDF and ZLC rats at 12 and 20 weeks of age. Similarly, IFN-gamma and IL-1beta protein levels were significantly increased in ZDF rats compared to ZLC rats at 30 weeks of age, but not at 12 and 20 weeks of age. Interleukin-1beta immunoreactivity in the ZDF rats predominantly increased in the dentate gyrus and CA1 region of the hippocampus compared to that of ZLC rats at 30 weeks of age. In addition, IL-1beta immunoreactive structures in ZDF rats at 30 weeks of age were detected near the astrocytes and microglia. Conclusion: These results suggest that chronic diabetes activates microglia and significantly increases pro-inflammatory cytokine levels in the hippocampus.